Łącko, woj. Bydgoszcz, stanowisko 6 — obozowisko z fazy I („AB") kultury pucharów lejkowatych. Z badań nad genezą rozwoju i systematyką chronologiczną kultury pucharów lejkowatych na Kujawach - Domańska, Lucyna; Kośko, Aleksander (Acta Universitatis Lodziensis. Folia Archaeologica, 1983)
This article, apart from presentation of information (in Chapter 1) obtained in the course of studies in 1973 (conducted by the Kujawy Expedition of the Archeology Department of Poznań University) at the camp from istage AB Funnel Beaker Culture, represents an attempt at assessment of the chronological position (Chapter 2) and the genetic position (Chapter 3) of the Kujawy materials from his time fragment. Analys is of features distinguishing the regional expressions of the AB stylist ics ("early-cup") leads to the conclusion that Łącko represents a younger stage of its development revealing elements of the "classical-cup" stylistics (the early Wiórek stylistics). In this period there is observed an intensification of inter-caltural contacts in the contact zone of ecumens of societies from the developed section of the early KPL (AB) stages and cultures from the Lengyel circle (the Malice group?). This process is legible in the sphere of rules of the technological-utilitarian culture (construction, flint products) and symbolic (magic). It can be presumed that In the period of Lack-settlement existenc e there was expanded the early-Neolithic acculturation of the Central-European Depression.